The Role of Training and Development with Employee Involvement in Improving Employee Performance at PT Torabika Eka Semesta - Nike Talitha Imtyaz Naila; Enawar Enawar; Yanthi Meitry Gunawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Background: In the current era of intensified global competition and digital transformation, the manufacturing sector faces mounting pressure to sustain productivity through effective human resource practices. PT Torabika Eka Semesta, a subsidiary of the Mayora Group operating in Indonesia's food and beverage industry, has recently experienced a decline in production-target achievement, indicating potential weaknesses in employee competency development and engagement. Objective: This study analyzes the effect of training and development and employee engagement on employee performance, both partially and simultaneously. Method: A quantitative associative research design was applied, using primary data collected through a structured questionnaire measured on a five-point Likert scale. Sample: A saturated sampling technique was used, yielding 80 respondents from the production department of PT Torabika Eka Semesta. Statistical analysis: Data were processed using SPSS version 27, including validity, reliability, classical assumption tests (normality, linearity, multicollinearity, heteroscedasticity), multiple linear regression, coefficient of determination, t-test, and F-test. Main findings: Training and development had a positive and significant effect on employee performance (t = 2.805; p = 0.006), employee engagement had a positive and significant effect (t = 4.866; p = 0.000), and both variables simultaneously influenced employee performance (F = 11.919; p = 0.000), with an adjusted R² of 0.236. Employee engagement emerged as the dominant predictor. Practical implications: These findings provide practical implications for managers at PT Torabika Eka Semesta and other manufacturing companies by emphasizing that continuous competency development programs combined with strategies to strengthen employee engagement can improve productivity, work quality, and organizational competitiveness. Originality/value: The study contributes to human resource management literature by empirically integrating training and development with employee engagement within the underexplored context of Indonesia's food and beverage manufacturing industry.